Bioinspired, Mechanically Robust Chemiresistor for Inline Volatile Organic Compounds Sensing. Issue 10 (10th August 2020) - Xu, Weiheng; Ravichandran, Dharneedar; Jambhulkar, Sayli; Franklin, Rahul; Zhu, Yuxiang; Song, Kenan
Abstract: There are advantages to polymer/nanoparticle composite‐based volatile organic compounds (VOCs) sensors, such as high chemical and physical stability, operability under extreme conditions, flexible use in manufacturing, and low cost. Nevertheless, their lower limit of detection due to thickness‐dependent diffusion has constrained their application. Inspired by the metaxylem in vascular plants and its vertical conduits and horizontal pits that enable efficient transpiration, a polymer/nanoparticle composite‐based sensor is fabricated with a controllable, spontaneously formed, hollow core for inline VOCs transportation, and porous microstructure for radial direction diffusion. The hollow core is surrounded by an inner porous layer (thermoplastic polyurethane (TPU)), a middle sensing layer (TPU/graphene nanoplatelets/multiwalled carbon nanotubes), and an outer mechanically durable layer (TPU). This multilayered structure shows a 600% higher response rate compared to a single‐layered composite fiber sensor, with a low limit of detection (e.g., ≈15 ppm for xylene) and high selectivity based on the Flory–Huggins interaction parameter. This flexible and stretchable sensor also demonstrates a dual parameter sensing capability from VOC concentrations and uniaxial strain deformation. Via a one‐step fiber spinning procedure, this self‐induced hollow fiber offers a unique method of microstructural design, which enables the detection of low‐concentration VOCs by polymer/nanoparticle‐based sensors. Abstract : Inspired by the transpiration mechanism in vascular plants, a spontaneously formed hollow‐porous polymer nanocomposite fiber is fabricated through dry‐jet wet spinning with controlled rheological behavior. The sensitivity shows a 600% increase due to the multilayer structural design and enables inline measurement of various low concentrated volatile organic compounds as well as dual parameter sensing under mechanical deformation.